GE_GERICHTE P/11618/2025 vom 17. September 2025 - GE Cour de justice (2025)
INSTRUCTION(ENSEIGNEMENT);DIFFAMATION;CALOMNIE;ABUS D'AUTORITÉ;DROIT DE LA FONCTION PUBLIQUE;RÉSILIATION | CPP.310; CP.173; CP.174; CP.177; CP.312